Pengaruh Penggunaan Media Pembelajaran Geoboard Terhadap Hasil Belajar Siswa Pada Keliling Dan Luas Bangun Datar Kelas III SD - Ayu Ningrum, Safrida Napitupulu (Pusdikra Publishing, 2021)
Selecting and using appropriate learning media certainly has an effect on the quality of learning and students’ learning outcomes. This research started from the reality at SD Negri 101919 Kuala Namu that teachers had not used the right learning media as a tool in explaining plane figure material, low students’ learning outcomes in mathematics subjects, difficulty understanding math lessons, lack of using learning media in explaining math subject matter. The objective of the research was to find out whether there was an effect of using geoboard learning media on students’ learning outcomes on the the plane figure circumference and area of grade III elementary school. This type of research was quantitative research with Quasi Experiment Research Type with Nonequivalent Control Group Design. The population in this study is all grade III students of SD Negeri101919 Kuala Namu with a total of 36 students. The sampling technique used in this research was the simple random sampling technique, while the sample in this research was class III A which amounted to 18 students as an experimental class and class III B which amounted to 18 students as a control class. The instrument used in the research was a multiple-choice form test. The data analysis technique used was a t-test that as preceded by a prerequisite test of analysis using a normality test and a homogeneity test. The prettest average score for the experimental class was 64,77 and the perettest of the control class learning outcomes was 50,05. Then the two classes were given different treatments, so the average posttest grade of experimental class learning outcomes was 85 and the control class was 75,05. Hypothesis testing was done with the t test. From the results of calculations obtained tcount > ttable (2,9 > 2,02). It can be seen that tcount > ttable, so Ho was rejected and Ha was accepted. So the results of this research conclusion that the results of students’ learning mathematics who used geoboard learning media were higher than the results of students’ learning mathematics who used conventional learning media.